Research Culture in Educational Institutions:Change for Better - Pandharipande, V. M. (Journal of Engineering Education Transformations, 2011)
The System of Ph.D. education is a matter of concern for most of the Universities in India and abroad. Universities are expected to do meaningful, application oriented research that will indirectly enhance the quality of Teaching Learning process at UG/PG Level, also. Our traditional education is a process of cloning that trains students to do what their Mentors do. Our traditional research methodology is ’text book oriented’ and it hardly bothers about ’application’ and benefits of research to the society, at large.